Measurement of airway responsiveness to methacholine: relative importance of the precision of drug delivery and the method of assessing response. Issue 3 (March 1993) - Beach, J R; Young, C L; Avery, A J; Stenton, S C; Dennis, J H; Walters, E H; Hendrick, D J
Abstract : BACKGROUND: The value of measuring airway responsiveness in asthma research is currently limited by the number of different methods used by different investigators, by the lack of a standardised method of expressing precision, and by an inability to equate the results of one method with those of another. METHODS: Two pairs of measurements of airway responsiveness to methacholine were performed in 20 asthmatic subjects, one pair using a dosimeter method (AR-D) and one pair using the conventional Wright nebuliser tidal breathing method (AR-W). The two methods normally use different techniques for quantifying changing levels in forced expiratory volume in one second (FEV1) after each dose of methacholine (the mean of the highest three of six measurements for AR-D, the lower of two measurements for AR-W), and different techniques for expressing measurements of airway responsiveness (the provoking dose (PD20) and the provoking concentration (PC20) respectively responsible for a 20% decrement in FEV1). RESULTS: The coefficient of repeatability (and hence precision) for the measurement of airway responsiveness was significantly better for AR-D (3.0) than for AR-W (10.9), but the technique for quantifying FEV1 contributed more to this than the technique for delivering methacholine. A PC20 of 1 mg/ml with AR-W was equivalent to a PD20 of 103 micrograms with AR-D. CONCLUSIONS: It is practical as well as desirable to compare the precision of different techniques for the measurement of airway responsiveness and to derive conversion factors so that results may be equated.